The Effect of Hypnotherapy in the Management of Scaling in Autistic Children - Dewi Sartika; Supriyana Supriyana; Tri Wiyatini; Masrifan Djamil; Endah Aryati Eko Ningtyas (Syntax Idea)
According to WHO in Indonesia there are 7-10% of children with special needs. Children with special needs have lower levels of dental and oral health and hygiene than normal children. Based on a survey in Velezuelan and a study in Malaysia, autistic children have calculus with poor criteria. Autism is one of the complex disorders of child development. Autistic children have problems with their behavior, one of which is hyperactivity or hyperactivity. Hypnotherapy is a method of treatment and healing commonly known as hypnosis. Hypnosis is one therapy that is expected to reduce the level of hyperactivity and cooperation in autistic children. This study aims to prove the effect of hypnotherapy in the management of scaling in autistic children by increasing children's cooperative attitudes and decreasing calculus index in autistic children. This research is a quasy experiment pre and post-test design ( Non-equivalent Control Group). Respondents amounted to 20 children divided into 2 groups. The data of the model test results were analyzed using paired t tests and independent t tests. Based on the results of the study, the effect of hypnotherapy on increasing the cooperative attitude of autistic children is with (P = 0.000), and decreasing the calculus index with (P = 0.000). And showed the delta value of the child's cooperative attitude (10.100) which was higher than the control group and calculus index (1.166) which was higher than the control group. The influence of hypnotherapy in the management of scaling in autistic children is characterized by an increase in the child's cooperative attitude and a decrease in the calculus index in autistic children.